Activation of the spinal and brainstem locomotor networks during free treadmill stepping in rats lacking dopamine transporter - Veshchitskii, Aleksandr; Shkorbatova, Polina; Mikhalkin, Aleksandr; Fesenko, Zoja; Efimova, Evgeniya V.; Gainetdinov, Raul R.; Merkulyeva, Natalia (Frontiers in Molecular Neuroscience, 2023)
Dopamine is extremely important for the multiple functions of the brain and spinal cord including locomotor behavior. Extracellular dopamine levels are controlled by the membrane dopamine transporter (DAT), and animals lacking DAT (DAT-KO) are characterized by hyperdopaminergia and several alterations of locomotion including hyperactivity. Neuronal mechanisms of such altered locomotor behavior are still not fully understood. We believe that in the hyperdopaminergic animals both spinal and brain neuronal networks involved in locomotion are modified. Using c-fos technique, we studied activated neuronal networks of the spinal cord and two brainstem structures related to the locomotor control and being under the strong dopaminergic influence: cuneiform nucleus (CnF) and ventrolateral periaqueductal gray (VLPAG), in wild type (DAT-WT) and DAT-KO rats. In the spinal cord, most c-fos-positive cells were located in the dorsal laminae II-IV, and in the central gray matter (laminae V-VI). No differences were revealed for the central areas. As for the dorsal areas, in the DAT-WT group, labeled cells mostly occupied the lateral region, whereas in the DAT-KO group c-fospositive cells were observed in both medial and lateral regions in some animals or in the medial regions in some animals. In the brainstem of the DAT-WT group, approximately the same number of labeled cells were found in the CnF and VLPAG, but in the DAT-KO group, VLPAG contained a significantly smaller number of c-fos-positive cells compared to the CnF. Thereby, our work indicates a disbalance in the sensorimotor networks located within the dorsal horns of the spinal cord as well as a disbalance in the activity of brainstem networks in the DAT-deficient animals.